Altered movement patterns but not muscle recruitment in moderately trained triathletes during running after cycling - Bonacci, J.; Blanch, P.; Chapman, A. R.; Vicenzino, B. (Journal of Sports Sciences, 2010)
Previous studies have shown that cycling can directly influence neuromuscular control during subsequent running in some highly trained triathletes, despite these triathletes' years of practice of the cycle-run transition. The aim of this study was to determine whether cycling has the same direct influence on neuromuscular control during running in moderately trained triathletes. Fifteen moderately trained triathletes participated. Kinematics of the pelvis and lower limbs and recruitment of 11 leg and thigh muscles were compared between a control run (no prior exercise) and a 30 min run that was preceded by a 15 min cycle (transition run). Muscle recruitment was different between control and transition runs in only one of 15 triathletes (<7%). Changes in joint position (mean difference of 3°) were evident in five triathletes, which persisted beyond 5 min of running in one triathlete. Our findings suggest that some moderately trained triathletes have difficulty reproducing their pre-cycling movement patterns for running initially after cycling, but cycling appears to have little influence on running muscle recruitment in moderately trained triathletes.